Blood Pressure and Risk of Cardiovascular Events in Patients on Chronic Hemodialysis: The CRIC Study (Chronic Renal Insufficiency Cohort). Issue 2 (August 2017) - Bansal, Nisha; McCulloch, Charles E.; Lin, Feng; Alper, Arnold; Anderson, Amanda H.; Cuevas, Magda; Go, Alan S.; Kallem, Radhakrishna; Kusek, John W.; Lora, Claudia M.; Lustigova, Eva; Ojo, Akinlolu; et al.
Abstract : We recently reported a linear association between higher systolic blood pressure (SBP) and risk of mortality in hemodialysis patients when SBP is measured outside of the dialysis unit (out-of-dialysis-unit-SBP), despite there being a U-shaped association between SBP measured at the dialysis unit (dialysis-unit-SBP) with risk of mortality. Here, we explored the relationship between SBP with cardiovascular events, which has important treatment implications but has not been well elucidated. Among 383 hemodialysis participants enrolled in the prospective CRIC study (Chronic Renal Insufficiency Cohort), multivariable splines and Cox models were used to study the association between SBP and adjudicated cardiovascular events (heart failure, myocardial infarction, ischemic stroke, and peripheral artery disease), controlling for differences in demographics, cardiovascular disease risk factors, and dialysis parameters. Dialysis-unit-SBP and out-of-dialysis-unit-SBP were modestly correlated ( r =0.34; P <0.001). We noted a U-shaped association of dialysis-unit-SBP and risk of cardiovascular events, with the nadir risk between 140 and 170 mm Hg. In contrast, there was a linear stepwise association between out-of-dialysis-unit-SBP with risk of cardiovascular events. Participants with out-of-dialysis-unit-SBP ≥128 mm Hg (top 2 quartiles) had >2-fold increased risk of cardiovascular events compared with those with out-of-dialysis-unit-SBP ⩽112 mm Hg (3rd SBP quartile: adjusted hazard ratio, 2.08 [95% confidence interval, 1.12–3.87] and fourth SBP quartile: adjusted hazard ratio, 2.76 [95% confidence interval, 1.42–5.33]). In conclusion, among hemodialysis patients, although there is a U-shaped (paradoxical) association of dialysis-unit-SBP and risk of cardiovascular disease, there is a linear association of out-of-dialysis-unit-SBP with risk of cardiovascular disease. Out-of-dialysis-unit blood pressure provides key information and may be an important therapeutic target. Abstract : Supplemental Digital Content is available in the text.